Moderate‐intensity exercise increases renalase levels in the blood and skeletal muscle of rats. Issue 6 (21st April 2020) - Tokinoya, Katsuyuki; Yoshida, Yasuko; Sugasawa, Takehito; Takekoshi, Kazuhiro
Abstract : Renalase is predominantly expressed in the kidney, where it plays a role in catecholamine metabolism and blood pressure regulation. Moderate‐intensity exercise (MEX) has been shown to increase the concentration of renalase in the blood and to reduce renal function in humans. Moreover, such exercise was also reported to increase catecholamine levels. Here, we examined renalase concentration in the blood and renalase expression levels in different organs after MEX in rats. Twelve male Wistar rats were made to run on a treadmill (MEX group) for 60 min at 20 m·min −1, after resting for 15 min. The control group rats were euthanized after resting on the treadmill. Tissue and blood samples were analyzed using western blotting, real‐time RT‐PCR and ELISA. Overall, the concentrations of renalase in the blood were significantly higher in the MEX group than that in the control group. Renalase expression was decreased in the kidney after 60 min of exercise, whereas the expression of renalase mRNA and protein in the extensor digitorum longus and plantaris muscles, respectively, increased after exercise. However, the expression of renalase in the other tissues examined did not change after acute exercise. In conclusion, we report that MEX for 60 min increases both renalase concentration in the blood and its expression in skeletal muscle. Abstract : The concentration of renalase in the blood and its expression in skeletal muscle were significantly increased in rats that underwent moderate‐intensity exercise as compared with the sedentary group, whereas renalase expression in the kidney decreased after exercise. Renalase expression in other tissues did not change after acute exercise.